Perancangan Sistem Informasi Laboratorium Pendidikan Teknik Elektronika FT-UNM - Ridwansyah Ridwansyah (Seminar Nasional LP2M UNM, 2019)
The development of the utilization of information and communication technology (ICT) is carried out at any time. Universities as a forum for the development of science and technology must innovate in the use and development of ICT. The laboratory as a place to improve student skills is not immune to this, especially in the form of laboratory equipment management. The utilization of information systems is important in the administration of practical activities in the laboratory. This is done so that the condition of laboratory equipment can be monitored. The design of laboratory information systems at the Department of Electronics Engineering Education, Faculty of Engineering, Makassar State University is carried out using the PIECES framework approach. Based on the results of this study, this information system can monitor the equipment condition of each laboratory's and its recapitulation is presented in tables and graphs